A imagem visual aplicada na publicidade e propaganda: uma experiência em projetos experimentais de graduação - Santos, Silvia Spagnol Simi dos (2008)
This study presents an investigation of the focused perception in visual communication. In order to understand how the creation and the reading of visual images got into the scientific field, the image genealogy of the Ancient Greece is revisited. Descartes and Kant are addressed to establish the basis that guide the theory of some current philosophers. The main objective of this research is the production and the perception of visual messages, which were analyzed through an experimental project. By means of the review of literature on the theories of language, especially those related to the visual language and the analysis of the object, this research seeks the discrimination between the processes of production and perception of visual images. Its purpose is to apprehend the established and the non-established perceptions of the world and finally, apply this analysis into publicity materials. As a conclusion, it is assumed that the visual language, which cannot be separated from the verbal language, is a persuasive resource that is largely applied by the publicity market to generate a double need